Frequency of urinary tract infections in type 2 diabetes patients receiving SGLT-2 inhibitors - Nazeer, Muhammad Qamar; Arif, Umair; Qaisar, Fahad; Afaq, Muhammad Farooq; Usman, Farukh; Ahmed, Nida Khurshid (Biological and Clinical Sciences Research Journal, 2025)
Urinary tract infection (UTI) is a clinically relevant concern in patients with type 2 diabetes mellitus (T2DM), particularly among those receiving sodium-glucose cotransporter-2 (SGLT-2) inhibitors. In Pakistan, many patients initially seek treatment from community pharmacies rather than hospitals, which may delay formal diagnosis and management. Objective: To determine the frequency of urinary tract infections among patients with type 2 diabetes mellitus receiving SGLT-2 inhibitor therapy. Methods: This descriptive cross-sectional study was conducted at the Department of Medicine, Bahawal Victoria Hospital, Bahawalpur, from 17 June 2025 to 7 October 2025. A total of 136 male and female patients aged 30 to 70 years with T2DM who had been receiving SGLT-2 inhibitors for more than three months were included. Pregnant women, patients with a history of coronary artery disease, current catheterization, recent UTI within the preceding two weeks, or spinal injuries were excluded. Midstream urine samples were collected in sterile containers and sent for microbiological examination. Urine culture was performed on cysteine-lactose-lysozyme-deficient agar, and the plates were incubated at 37°C for 24 hours. A consultant pathologist reviewed culture reports to confirm the presence or absence of UTI. Data were analyzed using descriptive statistics, and continuous variables were presented as mean ± standard deviation, while categorical variables were reported as frequencies and percentages. Results: The mean age of the participants was 55.48 ± 12.19 years. Of the 136 patients, 77 (56.62%) were male, and 59 (43.38%) were female. The mean body mass index was 27.60 ± 3.02 kg/m², while the mean duration of diabetes mellitus was 11.56 ± 4.31 years. Urinary tract infection was identified in 19 patients, yielding a frequency of 13.97% among T2DM patients receiving SGLT-2 inhibitors. Conclusion: Urinary tract infection was observed in a notable proportion of patients with type 2 diabetes mellitus receiving SGLT-2 inhibitors. These findings suggest the need for careful clinical monitoring and early recognition of UTI in this patient population to improve treatment outcomes.